An energy and exergy analysis of photovoltaic system in Bantul Regency, Indonesia - Arif Rahman Hakim; Wahyu Tri Handoyo; Putri Wullandari (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2018)
Energy and exergy analysis has been conducted on photovoltaic (PV) system in Bantul Regency, a special region of Yogyakarta, Indonesia. The PV exergy analysis was used to determine the performance of the PV system by considering environmental factors other than solar irradiance. This research aims to obtain values of exergy and energy efficiencies in the PV system. The experiment results show that the energy efficiency value produced by the PV system was 8.62–74.18%, meanwhile its exergy efficiency was 0.29%-9.40%, respectively. The value of exergy efficiency is lower than the value of energy efficiency. This result confirmed that the environmental factor greatly affects the output of the PV system. It can be concluded that high solar radiation does not always increase the production of exergy, since it is also influenced by the environmental temperature and the PV cells' temperature.